Effect of Lecithin on the Fibrinolytic System in Guinea-Pig Serum - Olesen, E. S (Thrombosis and Haemostasis, 1962)
Lecithin preparations from egg yolk or from soya beans added to guinea-pig serum which is subjected to isoelectric precipitation produce fibrinolytic activity in the precipitates in a manner similar to that previously reported for anionic polyelectrolytes. The possible physiological significance of this observation is discussed.